Management of central venous catheter - Jezova, Lubomira; Ziakova, Katarina (Profese Online, 2011)
Implementation of central venous catheterization system to the clinical practice represents considerable progress and benefit for the patient. On the other side central venous catheter is invasive method connected with skin tissue impairment direct entrance to central venous system with technical risks, infection and thrombosis complications.Aim: The aim of our study was find out differences between the national standards No. 48, 49 created by Ministry of health of Slovak Republic and the local standards, which are using in Intensive care Unit of Transplant and vascular surgery Clinic of Faculty Hospital in Martin. And also to identify the most often occurring complications related to insertion of central venous catheter.Methods: We used the method of audit (method of observation, measurement and documentation study respectively) to collect empirical data.Results: In contrast with standard no. 48 there is using transparent semipermeable film in dressing. C-vitamin clot is applied to the free inputs and there is not used antibiotic unguent. In the manipulation of central venous catheter, a patient is not in a horizontal position and in disconnecting of infusion sets are not used disintectant. The most often occuring complication was a haematoma in 66 %, pain in 60 % and leukocytosis in laboratory examination (which could be a sign of inflammatory process) in 63 % in our group of the patients.Conclusions: The differences found between standards MZ SR n. 48, 49, and work progresses on the intensive care unit do not adversely affect the course of the insertion of central venous catheter (CVC) and care of central venous access (CVA)and CVC. Using of nursing standards of CVC is important for providing the high-class and effective health care. Also is important that the standards should be designed to meet the nursing practice based on evidence.
Keywords: central venous catheter; nursing care; complications; standards